Arabic-Speaking Christians and Toledo, BCT MS Cajón 99.30 in High Medieval Spain - Martin, Geoffrey (Collectanea Christiana orientalia, 2021)
This article interprets the Arabic notes of a Christian who made a primer of Latin grammatical texts - primarily Donatus' Ars grammatica - in order to shore up his Latin vocabulary. The copyist on the whole offers excellent evidence for Latin learning among Iberia's Arabic-speaking Christians, who thrived in much of the peninsula between the tenth and thirteenth centuries.